Pengukuran Kualitas Informasi dengan Menerapkan Augmented Reality pada Media Promosi (Brosur) Berbasis Android - Miftahul Madani; Arief Setyanto; Amir Fatah Sofyan; Danang Tejo Kumoro (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
Augmented reality is a technology that is part of the development of the multimedia world that brings many ideas in various fields of promotion is no exception. The idea of using augmented reality in promotional media (brochures) that aims to improve the quality of information that is applied to the android platform one of them. The analytical method used in this study on validation testing is the product moment correlation technique, then the interval will be made as a measuring tool to determine the variable value of effectiveness, efficiency and satisfaction. The results concluded that the effectiveness variable showed at the number 59.817 on a scale > 52.85 - 61.442 which is very close to effective, the efficiency variable showed at the number 23.833 on a scale > 21.145 - 24.574 which is very close to efficient, and the satisfaction variable showed 47.417 at a scale > 42.285 - 49,142 which is very close to satisfying. Based on this, the use of augmented reality technology applied to promotional media can affect the level of quality of information and can display video and audio information on promotional media (brochures) STMIK Bumigora Mataram based on Android.